Fourth Ethiopia Economic Update : Overcoming Constraints in the Manufacturing Sector - World Bank Group (Washington, DC, 2015)
The Ethiopian economy continued its strong expansion in FY14 with real GDP growing by 10.3 percent. Growth was driven mainly by the services sector from the supply side and public investment from the demand side. At the same time, inflation has remained in single digits for the last two years on account of tighter monetary policy and lower international commodity prices. However, in recent months in 2015, domestic food prices are increasing partially as a result of shortage rainfall during the short rainy season. On the fiscal side, the budgetary stance at the general government level has been cautious. In an effort to adjust for the rising cost living, the FY15 budget incorporates an increase in public sector salaries after years of no increases which could also be the first step to adjust the balance between capital and recurrent expenditure. The salary increase accompanied by a supplementary budget in the middle of the fiscal year could potentially increase the budget deficit. The current account balance weakened. The deterioration is on account of a worsening trade deficit which was driven by weak export performance and large imports of capital goods for public investment programs. Goods exports showed positive growth in 2013-14 but rates remained far below their historical growth; furthermore, export growth fell into negative territory again in the last quarter of 2014 and first quarter of 2015. The strong economic growth in the past decade helped to reduce poverty significantly. The poverty headcount, measured by the national poverty line, fell from 38.7 percent in 2005 to 29.67 percent in 2011. Measured with the international poverty line (US$1.25 per day) Ethiopia saw the second fastest rate of reduction in Africa. Economic growth, particularly in agriculture, has been an important driver of poverty reduction in the last decade. Favorable weather conditions and improving terms of trade for rural producers have been reasons of this past trend supported by strong improvements in access to basic services and rural safety nets. Low levels of inequality have been maintained with the Gini coefficient remaining stable at 0.30.